An explanatory theory of power in inter-organisation relationships: evidence from the aerospace and defence industry. - Simpson, Deborah Catherine (Cranfield University, 2022)
This thesis concerns the phenomenon power, heralded the most fundamental yet contested phenomenon / concept in social science. The focus is establishing the essential qualities that describe, characterize, and explain power in inter- organisation relationships (IOR-power) to inform debates on the significance of IOR-power to supply chain performance. The thesis is founded on an iterative and critical synthesis of core academic perspectives spanning 50 years and 27 practitioner perspectives obtained from three field studies, unearthing meanings and experiences attributed to IOR-power. It is argued that IOR-power standing replete with unresolved contestations has been under-theorised and under- valued in the literature and in practice. An imbued distain for IOR-power is fuelled by an untenable dichotomisation of consensual IOR-influence and coercive IOR- power – unnecessarily stripping IOR-power of much of its potency – leaving both precariously sharing the burden of explaining IOR-behaviour wherein accounts thus far are insufficient to explain IOR-outcomes of interest. Underpinned by a dialectical critical realism perspective, the main contribution is a plausible theory of IOR-power, a fundamental explanatory process building block complemented by a conceptual framework supported by evidence from the aerospace and defence industry. Advancing alignment with natural-based power, IOR-power is more comprehensively claimed to be the combination of embedded individual behaviour, human creations, and Nature, at work exploiting resources in pursuit of goal attainment – an emergent, downwardly inclusive social and natural-based process governing IOR-outcomes. Accordingly, IOR-influence is distinct from but wholly integral to IOR-power that is rendered situated, negotiated, and indeterminate. IOR-power is conferred its full weight in explaining IOR-performance across economic, social, and environmental domains rendering adopted perspective and attribution salient in IOR-power accounts. The only antithesis of IOR-power is IOR-powerlessness wherein empowerment and disempowerment stand as theoretical bridges.
Bourlakis, Michael - Associate Supervisor
Keywords: supply chain management; aerospace and defence; dialectical critical realism; influence; agency; empowerment; performance